Intermediate algebra - Poole, Barbara (Prentice Hall, 1994)
This second edition is intended for intermediate algebra courses and developmental mathematics with an elemantary algebra prerequisite. The inclusion of historical notes, study units, margin exercises, pre-tests, calculator problems, challenge problems, end-of-chapter summaries and co-operative learning exercises should be of interest to students in the broader culture of mathematics and algebra.